Le mystère de Crawford Park-(Partie 3) - Voisine, John (Les Argoulets, 2024)
Keywords: Logement; Quartiers; Verdun

Montreal's Square Mile: the making and transformation of a colonial metropole - Anastakis, Dimitry; Kirkland, Elizabeth; Nerbas, Don (University of Toronto Press, 2024)
Keywords: Bourgeoisie; Golden Square Mile; Quartiers

La Belle Centenaire - Bolduc, Diane (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2024)
Keywords: Logement; Patrimoine; Sault-au-Récollet

Le parc Molson et ses abords - Bouchard-Dupont, Maude (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2024)
Keywords: Parcs; Rosemont

L'église Saint-Arsène il était une foi... - Desautels, Stéphanie (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2024)
Keywords: Rosemont; Églises

Un aperçu des résidents du Parc Amherst 1892-1921 - Gaudreau, Guy (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2024)
Keywords: Locataires; Logement; Rosemont

Le 1035 rue de Bellechasse: une coopérative trentenaire dans un bâtiment centenaire - Gouin, Christiane (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2024)
Keywords: Coopérative d'habitation de Montréal; Rosemont

La Halte de La Visitation - Goulet, Patrick (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2024)
Keywords: La Visitation (église); Patrimoine; Sault-au-Récollet

Une victorienne bien cachée! - Ménard, Céline (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2024)
Keywords: Famille; Logement; Sault-au-Récollet

Proprety and Power: Connecting the Dots - Olson, Sherry (Montreal's Square Mile: the making and transformation of a colonial metropole, 2024)
Keywords: Bourgeoisie; Golden Square Mile; Quartiers

Dans la rue. Une histoire du FRAPRU et des luttes pour le logement au Québec - Saillant, François (Écosociété, 2024)
Keywords: Groupes populaires; Logement

Gender and Social Relations in the City above the Hill - Sweeny, Robert C.H. (Montreal's Square Mile: the making and transformation of a colonial metropole, 2024)
Keywords: Bourgeoisie; Femmes; Golden Square Mile; Quartiers

Le bungalow, un témoin de l'histoire d'Anjou - Tessier, Stéphane (Il était une fois...Montréal-Nord, 2024)
issued: 2024-21-00
Keywords: Anjou; Banlieue

Westmount Station: Canadian Pacific history and future visioning - Hanna, David B. (The Westmount Historian, 2023)
Keywords: Canadien Pacifique; Commémoration; Gares

Inventories, Interiors, and Women’s Ambitions: Strategies of Property Ownership in Three Mid-19th Century Montreal Public Houses - Poutanen, Mary Anne (Urban History Review/Revue d'histoire urbaine, 2023)
Keywords: Femmes

Saint-Louis-Du-Mile-End. De la campagne à la ville (Bulletin de la Société d'histoire et de généalogie du Plateau-Mont-Royal, 2023)
issued: 2023-23-00
Keywords: Chemins de fer; Institution des sourds-muets; Logement; Mile End; Soeurs de la Providence

Ucal-Henri Dandurand et la pratique des ventes de sociétés immobilières à Montréal, au tournant du XXe siècle - Gaudreau, Guy (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2023)
Keywords: Publicité

La British and Canadian School de Montréal - MacLeod, Roderick; Poutanen, Mary Anne (Atlas historique du Québec. L'école au Québec, 2023)

La propriété en conflit: Justice et droit du logement à Montréal (1941-1980) - Mercier, Ian (Université du Québec à Trois-Rivières, 2023)
Keywords: Droit; Logement; Tribunaux

DAWSON, ARTHUR OSBORNE - Miller, Carman (Dictionnaire biographique du Canada, 2023)

Des origines à la Dépression. Quartier Crawford Park- (Partie 2) - Voisine, John (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2023)
Keywords: Quartiers; Verdun

La carrière Rhéaume 1909-1937 - Gaudreau, Guy (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2022)
Keywords: Carrière; Rosemont

Marion Nelson Crawford, la partenaire du notable fermier de la Côte-de-la-Visitation - Guilbault, Normand (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2022)
Number: 1
Keywords: Crawford; Alexander

“Far From Uninteresting”: Getting to Know the St. Lawrence River at Montreal During the Construction of the Victoria Bridge - Braiden, Heather (Urban History Review/Revue d'histoire urbaine, 2022)
In northern cities like Montreal, Quebec, Canada, the winters are long, and the construction season is condensed. In the mid-nineteenth century, knowing the St. Lawrence River’s seasonal variations and local construction customs helped railway and bridge builders save time and frustration during the very short working seasons. In this article, I investigate how technical and quasi-technical communications generated during the construction of the Victoria Bridge (1854–1860) are a rich source of urban knowledge. By examining visual and textual evidence in The Construction of the Great Victoria Bridge in Canada, I demonstrate how representations of the construction process are a tangible medium through which practical experience and a personal way of knowing the urban landscape are mediated. I argue that everyday experience and tacit knowledge move between social worlds and inform how audiences know and understand the colonial city.
Keywords: Victoria (pont)

Une belle histoire de coopération qui se poursuit - Archambault-Malouin, Diane (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2022)
Number: 11
Keywords: Ahuntsic; Arrondissements; Cartierville; Coopérative d'habitation de Montréal; Domaine Saint-Sulpice; La Familiale; Logement; Quartiers

La requalification du secteur industriel du Mile End, Montréal - Bur, Justin (Bulletin de l'AQPI, 2022)
issued: 2022-22-00
Keywords: Canadien Pacifique; Carrière; Chemins de fer; Mile End

St Anne's Market and its Underground Waters. Imagination and Innovation - Côté, Hélène (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Translators: _:n27 Translators: _:n62469
Keywords: Archéologie; Marchés; Sainte-Anne (marché)

Évolution du village de Saint-Jean-Baptiste - Deschambault, Gabriel (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2022)
issued: 2022-21-00
Keywords: Saint-Jean-Baptiste (village); Villages

TRUDEAU, JOSEPH-CHARLES-ÉMILE - English, John (Dictionnaire biographique du Canada, 2022)

La Ligue ouvrière catholique et la naissance de la paroisse Saint-André-Apôtre (première partie) - Ménard, Céline (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2022)
Number: 11
Keywords: Ahuntsic; Famille; Jeunesse ouvrière catholique (JOC); Ligue ouvrière catholique; Logement; Quartiers

À travers les frontières: la participation de Montréal au réseau d'échange inter-municipal sur les problèmes de logement dans les années 1930 - Racette, Jean-Christophe (Urban History Review / Revue d'histoire urbaine, 2022)
issued: 2022-23-00
Keywords: Logement

1844-1849. Montréal, the New Seat of Government - Roy, Alain (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Translators: _:n95 Translators: _:n62402
Keywords: Champ-de-Mars; Fonctionnaires; Gouverneurs; Monklands; Palais de justice; Parlement; Ramezay (château de)

Montréal, Hospitable Capital City - Roy, Alain (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Translators: _:n139 Translators: _:n62391
Keywords: Hôtellerie; Marchés

BÉÏQUE, FRÉDÉRIC-LIGORI - Vallières, Marc (Dictionnaire biographique du Canada, 2022)

Vivre dans une boîte à chaussure - Poitras, Jean (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2021)
Number: 10
Keywords: Logement

Going Together Like a Horse and Carriage: Rentier Marriages and Property Accumulation in Montréal, 1825-1903 - Sweeney, Robert C. H. (Histoire sociale / Social History, 2021)
Number: 112
Keywords: Famille; Logement; Mariage

L'énigmatique maison de ferme de la 23e avenue - Delagrave, Louis (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2021)
Number: 1
Keywords: Logement

Le docteur Ananie-Joseph Millier, un notable rosemontois méconnu - Gaudreau, Guy (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2021)
Number: 1
Keywords: Logement; Médecine; Quartiers; Rosemont

Alexander Crawford, le notable fermier de la Côte-de-la-Visitation - Guilbault, Normand (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2021)
Number: 1
Keywords: Crawford; Alexander

L’action des promoteurs immobiliers dans le processus de gentrification du Sud-Ouest de Montréal - Gaudreau, Louis; Houle, Marc-André; Fauveaud, Gabriel (Recherches sociographiques, 2021)
issued: 2021-01/2021-04
Keywords: Arrondissements; Gentrification; Le Sud-Ouest; Logement

Soutien et entraide. Les mouvements coopératifs et communautaires du Plateau de 1970 à 2000 (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2021)
issued: 2021-24-00
Keywords: Clinique des citoyens de Saint-Jacques; Cyclisme; Groupes populaires; Logement; Plateau Mont-Royal; Quartiers

Le marché Sainte-Anne et ses eaux souterraines. Imaginer et construire de façon innovatrice - Côté, Hélène (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Marchés; Sainte-Anne (marché)

Les premières maisons shoebox montréalaises de Rosemont et de Villeray - Gaudreau, Guy (Urban History Review / Revue d'histoire urbaine, 2021)
issued: 2021-23-00
Keywords: Quartiers; Rosemont; Villages; Villeray

Une famille pionnière de la rue Dandurand: celle de George Ineson - Guilbault, Normand; Gaudreau, Guy (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2021)
Number: 2
Keywords: Famille; Logement; Quartiers; Rosemont

Louis-Joseph Papineau’s Seigneurialism, Republicanism, and Jeffersonian Inclinations - Guimond, Olivier (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2021)
Number: 1
Keywords: Idéologies; Papineau; Louis-Joseph; Rébellions; Seigneurie

Ateliers à louer, le " phalanstère " d'Alfred Laliberté - Lacroix, Laurier (Les Cahiers des Dix, 2021)
Number: 75
Keywords: Laliberté; Alfred; Locataires; Logement; Peinture; Sculpture

COHEN, LYON - Lapidus, Steven (Dictionnaire biographique du Canada, 2021)

The Making of Habitat 67. A Tense Pas de Deux between Moshe Safdie and August Komendant - Legault, Réjean (Journal of the Society for the Study of Architecture in Canada / Le journal de la Société d'étude pour l'architecture au Canada, 2021)
Number: 1
Keywords: Béton; Expositions; Logement

Enjeux politiques de la frontière entre salubrité et insalubrité dans l'habitation montréalaise des années 1930 - Racette, Jean-Christophe (Revue d'histoire de l'Amérique française, 2021)
issued: 2021-22-00/2021-23-00
Keywords: Crise; Logement; Pauvreté

1844-1849. Montréal, nouveau siège du gouvernement - Roy, Alain (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Champ-de-Mars; Fonctionnaires; Gouverneurs; Monklands; Palais de justice; Parlement; Ramezay (château de)

Montréal, capitale accueillante - Roy, Alain (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Hôtellerie; Marchés

Luttes pour le droit au logement sur le Plateau - Vallée, Bernard (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2021)
issued: 2021-24-00
Keywords: Crise; Groupes populaires; Logement; Plateau Mont-Royal; Quartiers

Le rôle méconnu des promesses de vente dans le processus d'urbanisation à Montréal: le cas du village de Villeray au tournant du XXe siècle - Gaudreau, Guy (Urban History Review / Revue d'histoire urbaine, 2020)
issued: 2020-23-00
Keywords: Villages; Villeray

Divvying up Space: Housing Segregation and National Identity in Early Twentieth-Century Montréal - Sweeny, Robert C. H. (Sharing Spaces: Essays in Honour of Sherry Olson, 2020)
Keywords: Locataires; Logement; Quartiers

1840-1912: De la montée du Sault à la rue Lajeunesse: sept décennies de chemins de barrières... et quelques incendies - Lebleu, Jacques (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2019)
Number: 6
Keywords: Incendies; Routes; Rues

La première couronne montréalaise est sertie de maisons shoebox (Le Bulletin de la Société d'histoire Rosemont-Petite-Patrie, 2019)
Number: 1
Keywords: Conservation; Logement; Patrimoine; Quartiers; Rosemont

Carrières et pierre grise (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2019)
issued: 2019-22-00
Keywords: Carrière; De Lorimier (village); Géographie physique; Géologie; Histoire naturelle; Parcs; Plateau Mont-Royal; Quartiers; Travail; Villages; Églises

LAURIN, JAMES - Auger, Jean-François (Dictionnaire biographique du Canada, 2019)

"C'est providentiel!". Vendre le rêve suburbain à Montréal (1950-1970) - Bérubé, Harold (Cap-aux-Diamants, 2019)
issued: 2019-24-00
Keywords: Banlieue; Publicité

" De la fiction à… la réalité – de la télévision à… Laval-des-Rapides ": Mise en récit et mise en marché du rêve suburbain à Montréal, 1950–1969 - Bérubé, Harold (Quebec Studies, 2019)
Reporter: Quebec Studies
Keywords: Banlieue; Laval-des-Rapides; Publicité

La petite histoire, des origines jusqu'à 1925. Des carrières sous le parc Laurier - Côté, Julie; Cudia, Caroline (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2019)
issued: 2019-22-00
Keywords: Carrière; Parcs; Travail

FORTIN, SIFROY-JOSEPH - Fougères, Dany; Gagnon, Robert (Dictionnaire biographique du Canada, 2019)

Communauté Milton-Parc: How We Did It and How It Works Now - Kowaluk, Lucia; Piché-Burton, Carolle (Villages in cities: community land ownership, cooperative housing, and the Milton Parc story, 2019)
Keywords: Logement; Milton-Parc; Quartiers

MIGNAULT, ARTHUR - Litalien, Michel (Dictionnaire biographique du Canada, 2019)

Montreal Property-Owners of the 1850s: "Born or to Be Born" - Olson, Sherry (L'argent des familles. Pratiques et régulations sociales en Occident aux XIXe et XXe siècles, 2019)
Reporter: L'argent des familles. Pratiques et régulations sociales en Occident aux XIXe et XXe siècles
Keywords: Droit; Enfants; Famille; Logement

The influence of urban design theories in the transformation of urban morphology: Montreal from 1956 to 2018 - Racine, François (Journal of Urban Design, 2019)
Number: 6 Reporter: Journal of Urban Design
Keywords: Logement; Quartiers

CURRY, NATHANIEL - Sutherland, David A. (Dictionnaire biographique du Canada, 2019)

Introducing Canada to Urban Planning? Henry Vivian's Canadian Planning Tour, 1910 - Ulmer, Catherine Mary (Urban History Review / Revue d'histoire urbaine, 2019)
issued: 2019-21-00
Keywords: Logement

" Je me souviens " d’un domaine seigneurial à Ahuntsic - Archambault-Malouin, Diane (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2018)
Number: 4
Keywords: Ahuntsic; Communautés religieuses; Domaine Saint-Sulpice; Logement; Seigneurie; Sulpiciens

L'école Sainte-Odile: au coeur du "nouveau Cartierville" - M. Sénécal, Geneviève (Au fil d'ABC / SHAC, Société d'histoire d'Ahuntsic-Cartierville, 2018)
Number: 4
Keywords: Cartierville; Logement; Parcs; Quartiers; Rues

The Second World War: Wartime Production and War Efforts - Fahrni, Magda (Montreal: The History of A North American City, 2018)
Keywords: Armes; Conscription; Femmes; Guerre; Logement; Travail

The Modern City: 1840-1890 - Fougères, Dany (Montreal: The History of A North American City, 2018)
Keywords: Charte; Conseillers municipaux; Maires; Parcs; Places publiques; Quartiers; Saint-Antoine; Saint-Jacques; Saint-Laurent (quartier); Saint-Louis; Sainte-Anne; Sainte-Marie; Voirie; Élections

The years of dispersion - Fougères, Dany (Montreal: The History of A North American City, 2018)
Keywords: Côtes; Fortifications; Logement; Notre-Dame (paroisse); Routes; Rues; Villages

Permanence et renouvellement des familles ouvrières: le cas du Village-aux-Oies et de la rue Forfar, 1901-1921 - Giguère, Charles-Robert (Université du Québec à Montréal, 2018)
Keywords: Famille; Locataires; Logement; Mobilité résidentielle; Villages

Denis-Benjamin Viger (1774-1861). Patriote assagi par la richesse sans en être aveuglé - Lavallée, Martin (Montréal en tête, 2018)
issued: 2018-23-00
Keywords: Foretier; Pierre; Seigneurie; Testaments; Viger; Denis-Benjamin

Mount Royal: The Top of the Island - MacLeod, Roderick (Montreal: The History of A North American City, 2018)
Keywords: Mont Royal; Mont-Royal (parc); Parcs

La grève générale des charpentiers-menuisiers de Montréal, 1833–1834 : réévaluation d’un acte fondateur autour du concept de légitimité - Tremblay, Robert (Labour / Le travail, 2018)
Keywords: Charpentiers; Grèves; Libéralisme; Maçons; Menuisiers

On the Ruins of Hochelaga: 1535-1650 - Viau, Roland (Montreal: The History of A North American City, 2018)
Keywords: Autochtones; Cartier; Jacques; Chomedey de Maisonneuve; Paul (Maisonneuve; Paul de Chomedey de); Fourrure; Français; Hochelaga; Iroquoiens; Iroquois; Mance; Jeanne; Société de Notre-Dame de Montréal

La Montreal Investment Association, le Montreal Investment Trust et la seigneurie de Beauharnois (1866–1941) - LaRose, André (Canadian Historical Review, 2017)
Number: 1
Keywords: Fiducie

L'architecture du Plateau Mont-Royal (Bulletin de la Société d'histoire du Plateau-Mont-Royal, 2017)
issued: 2017-23-00
Keywords: Carmélites; Communautés religieuses; Logement; Plateau Mont-Royal; Quartiers; Églises

Cinquante ans de développement de la fonction résidentielle dans le Vieux-Montréal et les anciens faubourgs: quelles leçons en tirer ? - Ananian, Priscilla (Environnement Urbain / Urban Environment, 2017)
Reporter: Environnement Urbain / Urban Environment
Keywords: Faubourgs; Logement; Quartiers; Vieux-Montréal

Vendre la banlieue aux Montréalais: discours et stratégies publicitaires, 1950-1970 - Bérubé, Harold (Revue d'histoire de l'Amérique française, 2017)
issued: 2017-22-00/2017-23-00
Keywords: Anglophones; Banlieue; Francophones; Publicité

Corruption politique et clientélisme à Montréal de 1996 à 2011 : forces et dynamiques des institutions formelles et informelles à la lumière des travaux de la Commission Charbonneau - Gagné, Benoit (Université du Québec à Montréal, 2017)
Keywords: Maires

Contrôler le logement, contrôler la Ville: l’intervention en matière de salubrité des logements à Montréal, 1930-1939 - Racette, Jean-Christophe (Université de Montréal, 2017)
Keywords: Crise; Logement; Pauvreté

Les syndicats internationaux dans l’industrie de la construction au Québec (1887–1930) - Rouillard, Jacques (Labour / Le travail, 2017)
issued: 2017-23-00
Keywords: Charpentiers; Confédération des syndicats nationaux; Conseil des métiers et du travail de Montréal; Fédération des travailleurs et travailleuses du Québec (FTQ); Menuisiers

Expo 67: le choix du site et la forme des îles - Legault, Réjean (ARQ - Architecture Québec, 2016)
Number: 177
Keywords: Expositions

Repurposing buildings (The Westmount Historian, 2016)
Number: 2
Keywords: Conservation; Gares; Logement; Patrimoine

Apartment housing then and now: vignettes from Toronto and Montreal - Dennis, Richard (British Journal of Canadian Studies, 2016)
Number: 2
Keywords: Conservation; Logement

Tragédie à LaSalle: l'explosion du 1er mars 1965 - Gravel, Denis; Boucher, Isabelle (Éditions Histoire Québec, 2016)
Keywords: Arrondissements; Incendies; LaSalle; Logement

Seigneur absent, seigneur effacé? Louis-Joseph Papineau et la gestion de la Petite-Nation par l’entremise de Denis-Benjamin, son frère et agent seigneurial (1817-1854) - Guimond, Olivier (Histoire Québec, 2016)
Number: 2
Keywords: Papineau; Louis-Joseph; Seigneurie

Le père du célèbre Louis-Joseph Papineau: Joseph Papineau, premier en tout - Aubin, Georges (Montréal en tête, 2015)
issued: 2015-23-00
Keywords: Arpenteurs; Notaires

Shaping Time in the City: A Cultural History of Concrete Modernity in Montreal, 1903-2015 - Charles, Julia Morgan (Université McGill, 2015)
Keywords: Autoroutes; Béton; Port; Stade olympique

William Zeckendorf, Place Ville-Marie, and the Making of Modern Montreal - Nerbas, Don (Urban History Review / Revue d'histoire urbaine, 2015)
issued: 2015-21-00
Keywords: Gratte-ciel; Place Ville-Marie

La gestion seigneuriale de l'île de Montréal par les Sulpiciens au XVIIe siècle - Martel, Stéphan (Montréal en tête, 2014)
issued: 2014-23-00
Keywords: Communautés religieuses; Seigneurie; Sulpiciens

CURRIE, sir ARTHUR WILLIAM - Cook, Tim (Dictionnaire biographique du Canada, 2013)

Seigneurs and Landowners: An Ecclesiastical Economic Vision - Dickinson, John A. (The Sulpicians of Montreal: a history of power and discretion, 1657-2007, 2013)
Translators: _:n46695
Keywords: Communautés religieuses; Seigneurie; Sulpiciens

Une plongée vertigineuse dans l'histoire sociale de l'île de Montréal. Autour de la maison Brignon-Lapierre - Lapierre, Michel (Montréal en tête, 2013)
Number: 64
Keywords: Brignon-Lapierre (famille); Rébellions

Making Co-opville: Layers of Activism in Point St-Charles (1983-1992) - Vickers, Simon (Université Concordia, 2013)
Keywords: Groupes populaires; Pointe-Saint-Charles; Quartiers

La Deuxième Guerre mondiale: territoires d'armement et de l'effort de guerre - Fahrni, Magda (Histoire de Montréal et de sa région, 2012)
Keywords: Armes; Conscription; Femmes; Guerre; Logement; Travail

La ville moderne, 1840-1890 - Fougères, Dany (Histoire de Montréal et de sa région, 2012)
Keywords: Charte; Conseillers municipaux; Maires; Parcs; Places publiques; Quartiers; Saint-Antoine; Saint-Jacques; Saint-Laurent (quartier); Saint-Louis; Sainte-Anne; Sainte-Marie; Voirie; Élections

Les années de dispersion - Fougères, Dany (Histoire de Montréal et de sa région, 2012)
Keywords: Côtes; Fortifications; Logement; Notre-Dame (paroisse); Routes; Rues; Villages

Implantation d'un prototype de tableau de bord de gestion à la direction de soutien à la gestion de la Fédération des coopératives d'habitation intermunicipale du Montréal Métropolitain (FECHIMM) - Koffi, Yao Kouma (École nationale d'administration publique, 2012)

Sur les décombres d'Hochelaga, 1535-1650 - Viau, Roland (Histoire de Montréal et de sa région, 2012)
Keywords: Autochtones; Cartier; Jacques; Chomedey de Maisonneuve; Paul de (Maisonneuve; Paul de Chomedey de); Fourrure; Français; Hochelaga; Iroquoiens; Iroquois; Mance; Jeanne; Société de Notre-Dame de Montréal

Corner of Victoria Avenue & Sherbrooke (The Westmount Historian, 2011)
Number: 2
Keywords: Banque Royale; Banques; Magasins; Rues; Sherbrooke (rue)

La maison et ses dépendances (Les Argoulets, 2011)
Number: 2
Keywords: Nivard-De-Saint-Dizier (maison); Seigneurie; Verdun

Les différents propriétaires et leur histoire (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2011)
Number: 2
Keywords: Chapman; Joseph; Congrégation de Notre-Dame; Crawford; John; Dupuy; Zacharie; Greater Montreal Land Company; Logement; Nivard de Saint-Dizier; Marie-Anne; Nivard de Saint-Dizier; Étienne; Nivard-De-Saint-Dizier (maison); Steward Hunter; William; Verdun

Enforcing the Right to Healthy Housing: Recourse for Montreal Tenants Facing Health and Safety Problems at Home - Auchinleck, Jennifer (Université McGill, 2011)
Keywords: Locataires; Logement

L’opération 5000/15000 logements sociaux et communautaires: Une réponse au besoin en logements des ménages immigrants récents à Montréal, le cas de Côte-des-Neiges - Bahlouli, Abdelaziz (Université de Montréal, 2011)
Keywords: Côte-des-Neiges; Logement; Quartiers

L'évolution du capital immobilier au centre-ville de Montréal - Bernier, Lyne (Université du Québec à Montréal, 2011)
Keywords: Centre-ville; Quartiers

Le pont du domaine Saint-Gabriel - Douaire, Gilles (Histoire Québec, 2011)
Number: 3
Keywords: Communautés religieuses; Lachine (canal); Ponts; Saint-Gabriel (ferme); Seigneurie; Sulpiciens; Séminaire

Les premiers immeubles d’appartements de Montréal, 1880–1914. Un nouveau type d’habitation - Huppé, Isabelle (Urban History Review / Revue d'histoire urbaine, 2011)
issued: 2011-21-00
Keywords: Logement

La naissance d'un fief: Verdun - Loiselle, François (Les Argoulets, 2011)
Number: 2
Keywords: Seigneurie; Verdun

City Streets as Environmental Grid: The Challenge of Private Uses and Municipal Stewardship - Olson, Sherry (Metropolitan Natures: Environmental Histories of Montreal, 2011)
Keywords: Rues

Cinémas d’après-guerre - Pageau, Pierre (Continuité, 2011)
issued: 2011-22-00
Keywords: Cinéma

L'attrait pour le modèle de l'enclave résidentielle sécurisée dans la région montréalaise. que nous révèle le discours publicitaire sur le logement neuf? - Séguin, Anne-Marie (Cahiers de géographie du Québec, 2011)
Number: 154
Keywords: Logement

La maison et ses dépendances - Senez, Diane (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2011)
Number: 2
Keywords: Conservation; Patrimoine

Victoria Avenue in Westmount (The Westmount Historian, 2010)
Number: 1
Keywords: Casernes; Gares; Logement; Magasins; Rues; Westmount; Épicerie

Joseph Rielle (Riel). Maire de Verdun 1904-1905 - Billard, Guy (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2010)
Number: 2
Keywords: Arpenteurs; Maires; Quartiers; Verdun

Propriétaires et promoteurs à LaSalle: plus d'un siècle d'évolution économique - Boucher, Bruno; Gravel, Denis (Éditions Histoire Québec, 2010)
Keywords: LaSalle; Logement

La concertation autour du projet immobilier Porte Sainte-Marie à Montréal: le pari de la collaboration en marge du processus habituel - Cloutier, Geneviève; Sénécal, Gilles (Lien social et Politiques, 2010)
Number: 63
Keywords: Centre-sud (quartier); Logement; Quartiers

A Comparison of Workforce Housing Practices in Three Cities and their Applicability to Montreal - Lazarovic, Rebecca (Université McGill, 2010)
Keywords: Logement; Travail

Les déterminants de la valeur dans le marché immobilier montréalais: étude appliquée aux lignes de distribution câblées, à la végétation et aux types de rue - Montpetit, Guillaume (Université du Québec à Montréal, 2010)
Keywords: Logement; Quartiers; Île-des-Soeurs

Providing a Home and then Some: A study of Montreal's Homeownership Programme - Pinches, Brendan James (Université McGill, 2010)
Keywords: Logement

Réinvestir dans l'histoire. Trente ans de promotion immobilière dans l'arrondissement historique de Montréal - Poitras, Claire (Le Vieux-Montréal, un "quartier de l'histoire"?, 2010)
Keywords: Patrimoine; Quartiers; Vieux-Montréal

Louise Paradis: une femme à la tête du domaine Saint-Gabriel des Sulpiciens - Blondin, Yves (Les cahiers d'histoire de Pointe-Saint-Charles, 2009)
Keywords: Baux à ferme; Communautés religieuses; Famille; Femmes; Saint-Gabriel (ferme); Sulpiciens

La petite histoire du moulin à eau de la rivière Saint-Pierre et de ses meuniers - Charlebois, Paul-Yvon (Les cahiers d'histoire de Pointe-Saint-Charles, 2009)
Keywords: Communautés religieuses; Côtes; Meunerie; Sulpiciens

Château Ramezay: le passé continue - Delisle, André (Continuité, 2009)
issued: 2009-21-00
Keywords: Cartes et plans; Ramezay (château de)

La ferme Saint-Gabriel des sulpiciens à la Pointe Saint-Charles. Partie I: le Régime français - Douaire, Gilles (Les cahiers d'histoire de Pointe-Saint-Charles, 2009)
Keywords: Communautés religieuses; Pointe-Saint-Charles; Saint-Gabriel (ferme); Seigneurie; Sulpiciens

Reconstruire Montréal, rebâtir sa fortune - Dufaux, François; Olson, Sherry (Revue de Bibliothèque et Archives nationale du Québec, 2009)
Keywords: Faubourgs; Logement

L'accession à la propriété des jeunes familles à Montréal - Geoffroy, Caroline (École nationale d'administration publique, 2009)
Keywords: Logement

Investir, construire et habiter le monde. Les 25 ans de SITQ, histoire et perspectives - Marchand, Sarah; Linteau, Paul-André (Boréal, 2009)

Designing Sustainability for Whom? Recent Housing Development in Southwest Montreal - Poitras, Claire (Local Environment. The International Journal of Justice and Sustainability, 2009)
Number: 6
Keywords: Logement

Le légalisme à la sulpicienne - Savard, Rémi (Recherches amérindiennes au Québec, 2009)
Number: 1-2
Keywords: Autochtones; Communautés religieuses; Sulpiciens

Disputed Post-Industrial Landscapes: An Enquiry into the "Loft-Living" Cultural Model in Montréal's Saint-Henri - Tam, Edith (Université Concordia, 2009)
Keywords: Logement; Quartiers; Saint-Henri

Preservation of Westmount Homes built in the 1800s (The Westmount Historian, 2008)
Number: 1
Keywords: Conservation; Logement; Patrimoine; Quartiers; Westmount

WHA looks at some Prominent Westmounters (The Westmount Historian, 2008)
Number: 2
Keywords: Lait; Magasins; Port; Quartiers; Quincaillerie; Westmount

Les immeubles à appartements de l'île de Montréal, émergence et évolution d'une typologie, 1880-1914 - Huppé, Isabelle (Université du Québec à Montréal, 2008)
Keywords: Logement

Rapport sur la question du logement à Montréal; phase 2 - Roy, Christian (Laboratoire d'histoire et de patrimoine de Montréal, 2008)
issued: 2008-21-00
Keywords: Locataires; Logement; Pauvreté

L'héritage des soeurs des Saints-Nom de Jésus et de Marie à Outremont - Beauregard, Ludger (Histoire Québec, 2007)
Number: 3
Keywords: Communautés religieuses; Outremont; Quartiers; Soeurs des Saints Noms de Jésus et de Marie

Le Vieux-Montréal: une toute autre histoire - Chartrand, Roger (Septentrion, 2007)
Keywords: Quartiers; Vieux-Montréal

Seigneurs et propriétaires: une logique ecclésiastique de l'économie - Dickinson, John A. (Les Sulpiciens de Montréal: une histoire de pouvoir et de discrétion, 1657-2007, 2007)
Keywords: Communautés religieuses; Seigneurie; Sulpiciens

Conditions de logement des ménages immigrants et dynamiques métropolitaines à Montréal: une analyse multiniveau exploratoire - Leloup, Xavier (Cahiers québécois de démographie, 2007)
issued: 2007-21-00
Keywords: Logement

Equality and Urbanism: An Inquiry on Egalitarian Ethics in Planning with a Particular Reference to the Public Consultation Policy and the Overdale Approach to Equal Land-Use Opportunities of the Montreal Citizen's Movement - Pyun, Jin-Bak (Université Concordia, 2007)
Keywords: Rassemblement des citoyens et citoyennes de Montréal

Rapport sur la question du logement à Montréal; phase 1 - Roy, Christian (Laboratoire d'histoire et de patrimoine de Montréal, 2007)
issued: 2007-22-00
Keywords: Locataires; Logement; Pauvreté

Benny Farm: une vocation renouvelée - Barberese, Dino (Continuité, 2006)
issued: 2006-21-00
Keywords: Conservation; Logement; Patrimoine

Immeubles résidentiels à Montréal: l’art du compromis - Dufaux, François (Continuité, 2006)
issued: 2006-21-00
Keywords: Logement

A Gentleman of Substance: The Life and Legacy of John Redpath (1796-1869) - Feltoe, Richard (Dundurn Press, 2006)
Keywords: Hommes d'affaires; Redpath Sugar; Redpath; John; Sucre

Valeur hédonique des terrains à usage résidentiel unifamilial sur l'île de Montréal - Özdilek, Unsal (Université de Montréal, 2006)

The Affordable Housing Market in Montréal: a Market Analysis and Applicability Study of Inclusionary Zoning - Wang, Yun (Université de Montréal, 2006)
Keywords: Logement

Property Developers and the Robust Downtown: the Case of Four Major Canadian Downtowns - Charney, Igal (The Canadian Geographer / Le Géographe canadien, 2005)
Number: 3

Le Domaine. Une belle histoire qui se poursuit... Les loisirs du Domaine - Archambault-Malouin, Diane (Les Services du Domaine Inc., 2005)
Keywords: Domaine Saint-Sulpice; La Familiale; Logement

Famille, affaires et succession, les enjeux de la gestion seigneuriale au Canada. Étude de la région montréalaise des 17e et 18e siècles - Couvrette, Sébastien (Histoire Québec, 2005)
Number: 3
Keywords: Famille; Seigneurie

Le logement traditionnel à Montréal et à Glasgow: partage et différence - Dufaux, François (Montreal-Glasgow, 2005)
Keywords: Logement

Une culture matérielle riche dans le « Red Light » de Montréal: Inventaire et fouille archéologiques au faubourg Saint-Laurent MTL03-25-3, MTL03-25-2 et BjFj-121, 2003: Vieux-Montréal et faubourgs - Ethnoscop (Ville de Montréal, 2005)
Keywords: Faubourgs; Logement; Quartiers; Saint-Laurent (quartier)

Les marchés de construction notariés et les transformations de la sphère privée et de la sphère publique à Montréal entre 1700 et 1755 - Latouche, Pierre-Édouard (Université Laval, 2005)
Keywords: Notaires

On-Site Labor Productivity Estimation Using Neural Networks - Wang, Fang (Université Concordia, 2005)
Keywords: Travail

Le Domaine. Une belle histoire qui se poursuit... La Caisse du Domaine - Archambault-Malouin, Diane; Desbiens, Josée; Pronovost, Claude (Les Services du Domaine Inc., 2004)
Keywords: Banques; Caisses populaires; Desjardins; Alphonse; Domaine Saint-Sulpice; Logement

Le régime seigneurial à Montréal - Beaudoin, Léo (Montréal en tête, 2004)
issued: 2004-23-00
Keywords: Communautés religieuses; Seigneurie; Sulpiciens

La dynamique spatiale du marché des bureaux dans la région métropolitaine de Montréal de 1987 à 2001 - Gignac, Yannick (Université de Montréal, 2004)

Architectes et ingénieurs actifs à Montréal dans les années 1960 - Lortie, André (Les années 60: Montréal voit grand, 2004)
Keywords: Ingénieurs

Architects and Engineers Active in Montreal in the 1960s - Lortie, André (The 60s: Montreal Thinks Big, 2004)
Keywords: Ingénieurs

Montréal 1960; les singularités d'un archétype métropolitain - Lortie, André (Les années 60: Montréal voit grand, 2004)
Keywords: Métropole

Montreal 1960: The Singularities of a Metropolitan Archetype - Lortie, André (The 60s: Montreal Thinks Big, 2004)
Keywords: Métropole

Risky Spaces : The Montreal Fire Insurance Company, 1817-20 - Sweeny, Robert C. H. (Les territoires de l’entreprise / The Territories of Business, 2004)
Keywords: Assurance; Incendies

Spécial patrimoine bâti (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2003)
issued: 2003-23-00
Keywords: Bourgeoisie; Logement; Patrimoine; Quartiers; Rues; Verdun

La transmission du patrimoine seigneurial des familles du gouvernement de Montréal aux XVIIe et XVIIIe siècles - Couvrette, Sébastien (Université de Montréal, 2003)
Keywords: Famille; Notaires; Seigneurie

Le Domaine. Une belle histoire qui se poursuit... Trois coopératives... Tout un début! - Desbiens, Josée; Pronovost, Claude (Les Services du Domaine Inc, 2003)
Keywords: Chaurès-Louard; Berthe; Coopérative d'habitation de Montréal; La Familiale; Logement

La maison Bagg: inventaire archéologique au site BiFj-32, 1992: Vieux-Montréal et faubourgs - Ethnoscop (Ville de Montréal, 2003)
OCLC: 956636261
Keywords: Logement; Marchands

L'habitation type. Évolution de l'immeuble locatif pour les quartiers ouvriers: le cas de Verdun - Harton, Denis (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2003)
issued: 2003-23-00
Keywords: Logement; Quartiers; Verdun

Patrimoine industriel: le souffle de l’art - Lord, Denis (Continuité, 2003)
issued: 2003-21-00
Keywords: Patrimoine

The Road to Terrace Bank: Land Capitalization, Public Space, and the Redpath Family Home, 1837-1861 - Macleod, Roderick (Journal of Canadian Historical Association / Revue de la Société historique du Canada, 2003)
Number: 1
Keywords: Redpath (famille); Redpath; John

"Tuer le taudis qui nous tuera": crise du logement et discours sur la famille montréalaise d'après-guerre (1945-1960) - Bourbeau, Amélie (Université de Montréal, 2002)
Keywords: Logement; Pauvreté

Le déclin de la maison de fond de cour à Montréal, 1880–1920 - Carey, Luc (Urban History Review / Revue d'histoire urbaine, 2002)
issued: 2002-23-00
Keywords: Logement

L'intervention municipale dans le développement résidentiel, l'opération Habiter Montréal 1990-2001 - Gomez, Élodie (Université de Montréal, 2002)
Keywords: Logement; Évaluation foncière

Battles on the Homes Front: Montreal's Response to Federal Housing Initiatives, 1941-1947 - Lyons, Christopher M. (Université Concordia, 2002)
Keywords: Guerre; Logement

La transmission du patrimoine au Canada (XVIIe-XVIIIe siècle): qui sont les défavorisés? - Dépatie, Sylvie (Revue d'histoire de l'Amérique française, 2001)
Number: 4
Keywords: Famille

La montagne, capital et intérêts - Dubé, Catherine (Continuité, 2001)
issued: 2001-23-00
Keywords: Mont Royal; Mont-Royal (parc); Parcs

Déterminants de la valeur marchande des propriétés unifamiliales sur l'île de Montréal: évaluation de masse conjuguée aux SIG - Ozdilek, Unsal (Université du Québec à Montréal, 2001)
Keywords: Évaluation foncière

Impact des améliorations locatives sur la valeur d'un immeuble: le cas de Place Montréal Trust - Boilly, Jacques (Université du Québec à Montréal, 2000)
Keywords: Centres commerciaux

L'accès à la transaction immobilière: un des mécanismes du processus de ségrégation résidentielle ethnique - Paré, Sylvie (Recherches sociographiques, 2000)
Number: 3
Keywords: Logement

Housing Revitalization in Montreal: Are Condominium Conversions a Sustainable Alternative? - Swaby, Chantelle Simone (Université de Montréal, 2000)
Keywords: Logement